richiesmasher
Junior Member
- Joined
- Dec 15, 2017
- Messages
- 111
Hello, I have an equation here:
Solve (x-7)/2 + 6/x = 1/2
Now I've simplified as follows:
{x(x-7) + (6)(2)}/(2x) = 1/2
{x^2-7x +12}/(2x) = 1/2
Now I cross multiply and get
2(x^2-7x+12) = 2x
after factorizing the left hand side, I get
2 { (x-3) (x-4)} = 2x
and now I'm completely stuck, I'm trying to figure out what to do, should I have not factorized and brought across the 2x to make it a proper quadratic equation to use the formula to solve idk , someone please help
Solve (x-7)/2 + 6/x = 1/2
Now I've simplified as follows:
{x(x-7) + (6)(2)}/(2x) = 1/2
{x^2-7x +12}/(2x) = 1/2
Now I cross multiply and get
2(x^2-7x+12) = 2x
after factorizing the left hand side, I get
2 { (x-3) (x-4)} = 2x
and now I'm completely stuck, I'm trying to figure out what to do, should I have not factorized and brought across the 2x to make it a proper quadratic equation to use the formula to solve idk , someone please help
Last edited: